PW 0653 Build your balance: the devleopment of a falls prevention exercise video for older adults in western australia. (November 2018) - Macri, Chloe; Clark, Sonya; Wold, Catrina; Meade, Rachel
Abstract : Balance is a key risk factor for falls, with one quarter of all falls among older adults caused by poor balance. To increase awareness of the importance of balance in older adults living independently in Western Australia (WA), the Stay On Your Feet ® program, provided by Injury Matters and funded by the WA Department of Health, implements the 'Build Your Balance' campaign. Following a formative rapid review, a digital video was identified as a relevant resource to educate community members on safe balance exercises. The objective was to develop the Stay On Your Feet ® Build Your Balance Exercise Video that meets the needs of the target demographic. Consultations with health professionals (n=15) were undertaken via survey and telephone interviews to identify the needs of a balance resource. To develop the concept, consultation with a physiotherapist and an exercise physiologist was completed, and tested in two community focus groups (n=35) to assess content relevance. Consultations with health professionals concluded the video should contain both a health professional and older adult and needed to address exercise safety and correct technique. Results: From the community focus groups reported the preferred format and timeframe of a balance resource as a 15 min DVD. The content was identified as needing to cover the importance of balance exercises that range in fitness levels, safety information, and include a voice over of step-by-step exercise technique. The messaging needed to be positive and the balance exercises should be able to be incorporated into daily routines and exercise programs. The preferred video setting was a home environment and the cast was favoured to be relatable and use 'everyday people'. To best meet the needs of older adults, the Build Your Balance Exercise Video needs to be relatable, easily incorporated into daily routines and appropriate to complete independently.